2022
DOI: 10.1002/dep2.175
|View full text |Cite
|
Sign up to set email alerts
|

Earth’s oldest tsunami deposit? Early Archaean high‐energy sediments in the ca 3.48 Ga Dresser Formation (Pilbara, Western Australia)

Abstract: Dynamic sedimentary processes are a key parameter for establishing the habitability of planetary surface environments on Earth and beyond and thus critical for reconstructing the early evolution of life on our planet. This paper presents a sedimentary section from the ca 3.48 Ga Dresser Formation (Pilbara Craton, Western Australia) that contains high-energy reworked sediments, possibly representing the oldest reported tsunami deposit on Earth to date. Field and petrographic evidence (e.g. up to 20 cm large imb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…An alternative source of high‐velocity currents could be from storms, and a prior study has found evidence of tsunami deposits in the Dresser Fm. (Runge et al., 2022). However, chips have been observed in multiple layers (Figure 2; see also Noffke et al., 2013), suggesting a repeated event, and the frequency and magnitude of storms during the Archaean is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative source of high‐velocity currents could be from storms, and a prior study has found evidence of tsunami deposits in the Dresser Fm. (Runge et al., 2022). However, chips have been observed in multiple layers (Figure 2; see also Noffke et al., 2013), suggesting a repeated event, and the frequency and magnitude of storms during the Archaean is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative source of highvelocity currents could be from storms, and a prior study has found evidence of tsunami deposits in the Dresser Fm. (Runge et al, 2022).…”
Section: Stratigraphic Analysis Of the Rock Succession From Which Samplementioning
confidence: 99%
“…Interstitial carbonates were sampled from the ~3.49 Ga North Star Basalt (drill core 102 AIDP-1; 21°06'38"S, 119°06'4"E, French et al, 2015), the ~3.46 Ga Apex Basalt ("Schopf Locality" at Chinaman Creek; Schopf, 1993), the ~3.47 Ga Mount Ada Basalt and the ~3.35 Ga Euro Basalt (both near "Trendall Locality" at Shaw River;Hickmann et al, 2011), as well as from the Middle Basalt Member of ~3.48 Ga Dresser Formation (Dresser Barite Mine). Bedded sedimentary carbonates were sampled from the Dresser Formation at the "Tsunami Locality" (Runge et al 2022) near the Dresser Barite Mine, and the Euro Basalt at the east side of the Shaw River near the "Trendall Locality". Stromatolitic carbonates were collected from the Strelley Pool Formation at the western side of Shaw River.…”
Section: Sample Localitymentioning
confidence: 99%
“…The micritic carbonate is predominantly brownish and finely bedded. The association with pillow basalts indicates an interval of generally quiet-water sedimentation, although the succession might preserve the oldest record of a tsunami event on Earth(Runge et al 2022).…”
mentioning
confidence: 97%
“…Interstitial carbonates were sampled from the ~3.49 Ga North Star Basalt (drill core 102 AIDP-1; 21°06'38"S, 119°06'4"E, French et al, 2015), the ~3.46 Ga Apex Basalt ("Schopf Locality" at Chinaman Creek; Schopf, 1993), the ~3.47 Ga Mount Ada Basalt and the ~3.35 Ga Euro Basalt (both near "Trendall Locality" at Shaw River;Hickmann et al, 2011), as well as from the Middle Basalt Member of ~3.48 Ga Dresser Formation (Dresser Barite Mine). Bedded sedimentary carbonates were sampled from the Dresser Formation at the "Tsunami Locality" (Runge et al 2022) near the Dresser Barite Mine, and the Euro Basalt at the east side of the Shaw River near the "Trendall Locality". Stromatolitic carbonates were collected from the Strelley Pool Formation at the western side of Shaw River.…”
Section: Sample Localitymentioning
confidence: 99%